Physical fitness and development of female students in the Siberian region - Nikolaev, E.A.; Ponomarev, V.V.; Zhernakov, D.V.; Isaev, R.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to conduct a theoretical and statistical analysis of the physical fitness and physical development of female students in their first to third years of study in the Siberian region (using Krasnoyarsk State Agrarian University as an example), on the basis of which to develop corrective organisational and methodological recommendations and implement them in physical education practice. Methods and structure of the study. The study was conducted at the educational base of Krasnoyarsk State Agrarian University between 2024 and 2025. The sample size was 180 female students in their first to third years of study. Control groups of female students were formed using random sampling. The following methods were selected and used to organise and conduct the analytical study: analysis of scientific and methodological literature, pedagogical observation, surveys, questionnaires, physical fitness testing, measurement of physical development indicators, systematisation, abstraction, methods of mathematical statistics, etc. During the academic year, first- to third-year female students were tested for physical fitness according to the following indicators: push-ups, standing long jump, sit-ups per minute, 2000-metre run, 100-metre run, forward bend from a standing position, as well as measurements of physical development: height and weight, hand dynamometry (right and left hands) and measurement of heart rate at rest while sitting per minute. All of the above indicators were compiled and systematised in a table, on the basis of which the analysis was carried out. Results and conclusions. During the experimental work, 6 indicators of physical fitness and five indicators of physical development were analysed. The total number of various measurements exceeded 2,000 units. The significant factual material collected made it possible to identify the dynamics and state of physical fitness and physical development of first- to third-year female students in the Siberian region (using the example of students at Krasnoyarsk State Agrarian University). The physical development indicators of first- to third-year female students increased on average: in height by 1.3%, in body weight by 1.5%, in hand dynamometry: right hand by 25% and left hand by 26.6%. In terms of physical fitness, female students showed a significant increase on average in sit-ups per minute – 21.2% and forward bend from a standing position – 36.1%, strength indicators increased by 2.3% and speed-strength indicators by 3.1%, and speed indicators in the 100-metre run improved by 1.3%. These indicators allow us to conclude that female students show significant positive dynamics in the improvement of their physical development and physical fitness. Making additional methodological adjustments to the physical education programme for female students in the Siberian region (using Krasnoyarsk State Agrarian University as an example) will increase the effectiveness of the growth in physical development and physical fitness indicators for females by their third year of university.